2012
DOI: 10.1128/aac.06003-11
|View full text |Cite
|
Sign up to set email alerts
|

Efflux Pumps of Mycobacterium tuberculosis Play a Significant Role in Antituberculosis Activity of Potential Drug Candidates

Abstract: ABSTRACTActive efflux of drugs mediated by efflux pumps that confer drug resistance is one of the mechanisms developed by bacteria to counter the adverse effects of antibiotics and chemicals. To understand these efflux mechanisms inMycobacterium tuberculosis, we generated knockout (KO) mutants of four efflux pumps of the pathogen belonging to diff… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
99
1
1

Year Published

2012
2012
2024
2024

Publication Types

Select...
7
2
1

Relationship

1
9

Authors

Journals

citations
Cited by 134 publications
(108 citation statements)
references
References 35 publications
(40 reference statements)
1
99
1
1
Order By: Relevance
“…Inclusion of verapamil in drug susceptibility assays results in a marked decrease in the MIC for bedaquiline and clofazimine (144). Knockout studies have further implicated efflux pumps such as Rv1218c, Rv3065, Rv0849, and Rv1258c as important mechanisms of resistance to various chemical classes of drug compounds in M. tuberculosis (145,146). A recent study demonstrated increased expression of 15 EP-encoding genes, from various classes, in drug-susceptible and drug-resistant strains compared to reference, laboratory grown strains (110).…”
Section: Energy Metabolism and Drug Effluxmentioning
confidence: 99%
“…Inclusion of verapamil in drug susceptibility assays results in a marked decrease in the MIC for bedaquiline and clofazimine (144). Knockout studies have further implicated efflux pumps such as Rv1218c, Rv3065, Rv0849, and Rv1258c as important mechanisms of resistance to various chemical classes of drug compounds in M. tuberculosis (145,146). A recent study demonstrated increased expression of 15 EP-encoding genes, from various classes, in drug-susceptible and drug-resistant strains compared to reference, laboratory grown strains (110).…”
Section: Energy Metabolism and Drug Effluxmentioning
confidence: 99%
“…We have constructed knockout (KO) mutants lacking the different classes of efflux pumps of M. tuberculosis as follows. Rv1258c (KO1) and Rv0849 (KO6) are major facilitator superfamily (MFS) efflux pumps, Rv1218c (KO5) belongs to the ATP-binding cassette (ABC) superfamily, and Rv3065 (K07) belongs to the small multidrug resistance family (6,7). We investigated the contributions of these efflux pumps of M. tuberculosis towards intrinsic resistance to various PSI by comparing the in vitro activities of selected drugs on wild-type (WT) M. tuberculosis and the efflux pump KO mutants.…”
mentioning
confidence: 99%
“…A variety of compounds that have demonstrated activity against either resistance-nodulation-division (RND) pumps or ABC transporter-type systems were tested. Specifically, phenylalanine-arginine ␤-naphthylamide (PA␤N) (11), 1-(1-naphthylmethyl)-piperazine (NMP) (12), reserpine (13), probenecid (14), verapamil (15), and gemfibrozil (16) were all tested for their abilities to potentiate MB-1 activity in the adaptation assay. Using concentrations that were previously shown to affect the activities of various efflux pumps, improvements in MB-1 activity were not observed when it was combined with PA␤N, NMP, probenecid, verapamil, or gemfibrozil.…”
mentioning
confidence: 99%